2017
DOI: 10.1002/aenm.201602143
|View full text |Cite
|
Sign up to set email alerts
|

Photogenerated Carrier Mobility Significantly Exceeds Injected Carrier Mobility in Organic Solar Cells

Abstract: Charge transport in organic photovoltaic (OPV) devices is often characterized by space-charge limited currents (SCLC). However, this technique only probes the transport of charges residing at quasi-equilibrium energies in the disorderbroadened density of states (DOS). In contrast, in an operating OPV device the photogenerated carriers are typically created at higher energies in the DOS, followed by slow thermalization. Here, by ultrafast time-resolved experiments and simulations it is shown that in disordered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
129
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 86 publications
(137 citation statements)
references
References 40 publications
7
129
1
Order By: Relevance
“…First of all, with an electron mobility of about 103cm2 normalV1normals1 and a hole mobility of about 104cm2 normalV1normals1, the mobility contrast is well documented . Second, because of the semicrystalline nature of P3HT:PCBM with a relatively low energetic disorder, charge extraction and recombination are well described by quasiequilibrium concepts, so that drift–diffusion simulations lead to meaningful results . Third, the bimolecular recombination strength can be adjusted via the preparation conditions, in particular, the drying rate of the solvent and the application of thermal annealing .…”
Section: Resultsmentioning
confidence: 99%
“…First of all, with an electron mobility of about 103cm2 normalV1normals1 and a hole mobility of about 104cm2 normalV1normals1, the mobility contrast is well documented . Second, because of the semicrystalline nature of P3HT:PCBM with a relatively low energetic disorder, charge extraction and recombination are well described by quasiequilibrium concepts, so that drift–diffusion simulations lead to meaningful results . Third, the bimolecular recombination strength can be adjusted via the preparation conditions, in particular, the drying rate of the solvent and the application of thermal annealing .…”
Section: Resultsmentioning
confidence: 99%
“…This ensures that the starting point of the time-resolved measurement is an excited CT complex at the (isolated α-6T):C 60 interface, instantaneously creating an electron in C 60 and a hole in isolated α-6T. [25,26] Before we proceed with the detailed analysis of these kinetics, we highlight that these measurements were performed Figure 1. We have previously experimentally demonstrated that these traces represent the cumulative amount of photogenerated charge collected at the electrodes.…”
Section: Time-resolved Charge Extractionmentioning
confidence: 99%
“…Melianas et al found ν 0 around 1 × 10 13 s −1 for electron transport in PCBM and N2200, whereas ν 0 around 1 × 10 10 to 1 × 10 11 s −1 was found for hole transport in a range of polymer OSC. [24,25] Hence, irrespective of the precise meaning of ν 0 , the implication of the findings in Figure 4 is that n-type OSC might eventually become superior to their p-type counterpart if one succeeds to reach the end of the model curves in Figure 4, that is, reach a relative doping concentration ≈10% without compromising morphology.…”
Section: Wwwadvelectronicmatdementioning
confidence: 99%